2014
DOI: 10.1016/j.cpme.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Oxy-nitroso shielding burst model of cold atmospheric plasma therapeutics

Abstract: Cite this article as: David B Graves, Oxy-nitroso shielding burst model of cold atmospheric plasma therapeutics, Clinical Plasma Medicine, http://dx. AbstractIt is postulated that cold atmospheric plasma (CAP) can trigger a therapeutic shielding response in tissue by creating a time-and space-localized, burst-like form of oxy-nitrosative stress on near-surface exposed cells through the flux of plasma-generated reactive oxygen and nitrogen species (RONS). RONS-exposed surface layers of cells communicate to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 96 publications
0
62
0
1
Order By: Relevance
“…However, the dominating role of ROS and RNS is established and demonstrated by several experimental setups independent on the specific plasma device used [5,6]. Generation of ROS and RNS is mainly referable to atmospheric oxygen and nitrogen which are part of the working gas in air-based plasma sources but is also admixed into the plasma in the case of noble gas-based plasma sources if they are working at open atmospheric conditions.…”
Section: Biologically Active Plasma Components and Basic Mechanisms Omentioning
confidence: 99%
“…However, the dominating role of ROS and RNS is established and demonstrated by several experimental setups independent on the specific plasma device used [5,6]. Generation of ROS and RNS is mainly referable to atmospheric oxygen and nitrogen which are part of the working gas in air-based plasma sources but is also admixed into the plasma in the case of noble gas-based plasma sources if they are working at open atmospheric conditions.…”
Section: Biologically Active Plasma Components and Basic Mechanisms Omentioning
confidence: 99%
“…the destruction of biofilms [15] and tumours [16] in the order of 10s of micrometres to millimetres in thickness. APPJ deactivation of biofilms and tumours are often explained by surface cell layers transmitting signals deeper within tissue through cell-to-cell communication [17,18]. Using a synthetic tissue and cell model, we have shown that a He APPJ can directly interact with cells in the sub-surface of tissue (~150 m) [19].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that NT-APP treatment significantly reduces the size of solid cancerous tumors in the order of mm in thicknesses [6,11]. Initially, these results seem surprising because (i) the highlyreactive RONS, such as the hydroxyl radical (OH•) that induce significant cell damage, have relatively short lifetimes and diffusion distances [12], and (ii) the NT-APP treatment of solid organic materials is typically limited to the uppermost (first few nm) of the surface [13]. Therefore, initially it is difficult to reconcile how NT-APP treatment can penetrate into a solid tumor target of mm in thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The 'deeper' effects of NT-APP into solid tumors of several mm in thickness can potentially be explained by cell-cell communication [12,14,15]. In this scenario, cells stimulated at the surface of tissue by the NT-APP treatment, transmit signals deeper into the tumor through cellular signaling processes.…”
Section: Introductionmentioning
confidence: 99%